Counsellee’s experience of cancer genetic counselling with pedigrees that automatically incorporate genealogical and cancer database information - Stefansdottir, Vigdis (J Community Genet, 2016)
While pedigree drawing software is often utilised in genetic services, the use of genealogical databases in genetic counselling is unusual. This is mainly because of the unavailability of such databases in most countries. Electronically generated pedigrees used for cancer genetic counselling in Iceland create pedigrees that automatically incorporate information from a large, comprehensive genealogy database and nation-wide cancer registry. The aim of this descriptive qualitative study was to explore counsellees’ experiences of genetic services, including family history taking, using these electronically generated pedigrees. Four online focus groups with 19 participants were formed, using an asynchronous posting method. Participants were encouraged to discuss their responses to questions posted on the website by the researcher. The main themes arising were motivation, information and trust, impact of testing and emotional responses. Most of the participants expressed trust in the method of using electronically generated pedigrees, although some voiced worries about information safety. Many experienced worry and anxiety while waiting for results of genetic testing, but limited survival guilt was noted. Family communication was either unchanged or improved following genetic counselling. The use of electronically generated pedigrees was well received by participants, and they trusted the information obtained via the databases. Age did not seem to influence responses. These results may be indicative of the particular culture in Iceland, where genealogical information is well known and freely shared. Further studies are needed to determine whether use of similar approaches to genealogical information gathering may be acceptable elsewhere. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-016-0271-7) contains supplementary material, which is available to authorized users.